L'Antiquité classique - Cumont, Franz; Carnoy, Albert Joseph; Bidez, Joseph; Fondation universitaire de Belgique.; Belgium.; Rijksuniversiteit te Gent.; Université de Liège. (Impr. Oleffe, 1932)
Includes section "Comptes rendus."
Editors: Dec. 1932- J. Bidez, A. Carnoy, F. Cumont and others
Printed in Louvain, by Marcel Istas, Dec. 1932-Apr. 1933; Wetteren, De Meester, Nov. 1933-
Some vols. published in parts, 2008-
Includes section "Comptes rendus."
Contributions in French, Dutch, German, etc
Keywords: Classical antiquities / Periodicals.